Factors influencing caregiver burden during perioperative care for children with pediatric central nervous system tumors: an analysis of multidimensional burden and associated determinants - Yang, Yanjun; Fu, Jiahui; Fu, Yuwen; Fu, Jia (Frontiers in Pediatrics, 2025)
ObjectivesTo investigate the care burden of caregivers of children with central nervous system (CNS) tumors during the perioperative period and analyze the influencing factors of this burden.MethodsThis study enrolled primary caregivers of perioperative children with CNS tumors who underwent neurosurgery at Peking University International Hospital between December 2019 and July 2021. Data were collected via questionnaires (on admission and before discharge) and semi-structured interviews. The Zarit Burden Interview (ZBI-Chinese version) was used to measure care burden. Statistical analyses included the Shapiro–Wilk normality test, paired t-test, one-way analysis of variance (ANOVA), and stepwise regression. Semi-structured interview data were analyzed using Colaizzi's seven-step phenomenological approach.ResultsAmong the 67 primary caregivers enrolled in this study, the mean care burden score was 29.57 ± 7.22 on admission and 33.90 ± 7.89 before discharge (paired t = 4.212, P < 0.001), with most scores falling within the mild burden range (20–39 points). Three main factors influencing pre-discharge care burden were identified via stepwise regression: postoperative nutritional disorders (β = 0.213, P = 0.071, near statistical significance), current employment status of caregivers (β = 0.264, P = 0.022), and length of hospital stay (β = 0.256, P = 0.028). Qualitative analysis extracted five themes: navigating the medical system (logistical/access challenges), heavy psychological burden, lack of care knowledge, family-economic pressure, and avoidance of future uncertainty.ConclusionCaregivers of the children with pediatric CNS tumours experience significant perioperative care burden, which was higher before discharge than on admission. Interventions targeting postoperative nutritional management, caregiver employment support, and shortened hospital stays (when clinically feasible) may reduce burden. Strengthening caregiver education, psychological support, and social security systems is also recommended.